A novel mechanical inclinometer device to measure acetabular cup inclination in total hip arthroplasty. (16th November 2020) - van Duren, B. H.; Al Ashqar, M.; Lamb, J. N.; Pandit, H. G.; Brew, C.
Abstract: It is well recognised that acetabular cup orientation influences patient function and implant survival post-THR. Reliable intra-operative determination of cup orientation remains a challenge. We describe the design and testing of a novel mechanical inclinometer to measure intra-operative acetabular cup inclination. The aim was to design a generic inclinometer to measure acetabular inclination to within + 5° without requiring modification to existing instrumentation while remaining easy to handle, robust/reusable, and sterilizable. The device was drafted using CAD software, prototyped using a 3D printer and constructed using stainless steel. Two experiments were undertaken to test accuracy: (1) the absolute accuracy was tested; (2) placement of an acetabular component using the device was compared to a freehand technique using a sawbone pelvis. 18 surgeons were asked to place an uncemented acetabular cup in a saw bone pelvis to a target of 40°. The average root-mean-square error was 1.1° (SD: 0.9°). Comparison showed that with the freehand component placement 50% of the surgeons were outside the specified range (35°–45°) where all participants achieved placement within range when using the inclinometer. This work demonstrates that the design and initial testing of a mechanical inclinometer which is suitable for use in determining the acetabular cup inclination in THR.